Europe meets Asia - Asia meets Europe: What's the point of interregional dialogue and cooperation? - Hanns Günther Hilpert (Stiftung Wissenschaft und Politik (SWP), 2004)
From October 7-9 European and East Asian heads of state and government met at the Asia-Europe Meeting (ASEM) in the Vietnamese capital of Hanoi for their fifth inter-regional summit. Following the eastern expansion of the EU and northern expansion of the ASEAN community, the number of participating states has grown considerably to 38. Considering the size of the summit, the time invested by each of the heads of government to travel to and participate in it and the vague and non-binding final declaration that has once again come out of it, one is left questioning the sense and purpose of such mammoth summits. Moreover, allowing Burma to become a participating state despite European opposition has cast a dark shadow over the political dialogue between the two major regions. But the European-Asian process of dialogue and cooperation should not be solely evaluated based on the past summit. The strong economic ties between the two continents and the common interest in multilateralism as the guiding principle of global governance are among the positive, forward-looking elements of ASEM that go beyond the summit. (SWP Comments / SWP)
Keywords: 320